Perencanaan Program Interpretasi Lingkungan Di Kawasan Wisata Danau Linting Kabupaten Deli Serdang - Musawir Nasution; Pindi Patana; Yunus Afifuddin (Program studi Kehutanan USU, 2015)
Linting Lake is one of the tourism area that have big potential need more planning for better management. Research of environmental interpretation program in the Linting Lake had never been done before.The research is important to assesment for existing potentiality. Potential of ecotourism and interpretation program identified to used the obsevation method and analyzed as according scored criteria which have passed to visitors. result of research have indicated the potential ecotourism existed in Lunting Lake area are natural beauty, biodiversity of flora and fauna. The management area have executed by leader of the village and helped by local society lived around of area.Key words: potential tourism, interpretation program, management area